Tunable LED Lighting With Five Channels of RGCWW for High Circadian and Visual Performances - Jingxin Nie; Zhizhong Chen; Fei Jiao; Chengcheng Li; Jinglin Zhan; Yifan Chen; Yiyong Chen; XiangNing Kang; Yongzhi Wang; Qi Wang; Weimin Dang; Wentian Dong; et al. (IEEE Photonics Journal, 2019)
In this study, red, green, cyan, warm white and cool white (RGCWW) LEDs are individually controlled to simulate dynamic daylight. The spectral power distributions (SPDs) are measured for both the daylight and the mixed white light. The correlated color temperature (CCT), circadian action factor (CAF) curves in the daytime of the mixed white LED almost overlap to those of daylight with a small error of about 1%. The CIE chromaticity coordinates of the mixed white light are distributed along the Planckian locus with a little deviation below 0.003. Also, its color rendering index (CRI) is above 90. The RGCWW five-chip LEDs of high circadian and visual performances will benefit to synchronize circadian rhythm in closed environment during long time without daylight, combined with better mood and alertness. The simulation errors and development trend of the mixed lighting are discussed.